Computing with biological switches and clocks - Dalchau, N; Szép, G; Hernansaiz-Ballesteros, R; Barnes, C; Cardelli, L; Phillips, A; Csikász-Nagy, A (Springer Netherlands, 2018)
The complex dynamics of biological systems is primarily driven by molecular interactions that underpin the regulatory networks of cells. These networks typically contain positive and negative feedback loops, which are responsible for switch-like and oscillatory dynamics, respectively. Many computing systems rely on switches and clocks as computational modules. While the combination of such modules in biological systems leads to a variety of dynamical behaviours, it is also driving development of new computing algorithms. Here we present a historical perspective on computation by biological systems, with a focus on switches and clocks, and discuss parallels between biology and computing. We also outline our vision for the future of biological computing.